Pernikahan dini perspektif hukum Islam dan hukum positif - Sanusi, Anwar; Haqiqi Amirulloh, Luqman (AL-MUQARANAH, 2024)
Islam strictly speaking does not have rules that determine the age limit for marriage, based on Islamic law basically all age levels can enter into marriage. In Islam, the conditions for marriage are 'aqil and puberty which do not look at age limits. The method used is library research, namely by reading and studying books and writings that are related to the object of discussion, namely early marriage according to Islamic law and statutory regulations in Indonesia. The results of this research include: Ulama have different opinions regarding the age of marriage, including: Most Maliki madzhab ulama are of the opinion that the age limit for menstruation for women and men is 17 years or 18 years. Abu Hanifah believes that the age of puberty is 19 years or 18 years for men and 17 years for women. Imam Syafi'i, Ahmad, Ibnu Wahab and Jumhur are of the opinion that this is at the perfect age of 15 years. According to Marriage Law no. 1/1974 as a positive law in force in Indonesia, sets the age limit for marriage at 19 years for men and 19 years for women. In article 6 paragraph (2), it is stated that a person is said to be an adult if they reach the age of 21 years, so that in carrying out a marriage there is no need to obtain permission from both parents. The problem of early marriage in Indonesia according to Islamic law and Law no. 1 of 1974 concerning Marriage is based on the interests of children's rights, so that children can spend their time playing and studying. Apart from that, it is also necessary to pay attention to the impacts caused by early marriage, because they are not mature in thinking and resolving problems in marriage. So the goal of a mawwadah and rahmah marriage is not achieved optimally.